Primordial metallic melt in the deep mantle. Issue 8 (25th April 2016) - Zhang, Zhou; Dorfman, Susannah M.; Labidi, Jabrane; Zhang, Shuai; Li, Mingming; Manga, Michael; Stixrude, Lars; McDonough, William F.; Williams, Quentin
Abstract: Seismic tomography models reveal two large low shear velocity provinces (LLSVPs) that identify large‐scale variations in temperature and composition in the deep mantle. Other characteristics include elevated density, elevated bulk sound speed, and sharp boundaries. We show that properties of LLSVPs can be explained by the presence of small quantities (0.3–3%) of suspended, dense Fe‐Ni‐S liquid. Trapping of metallic liquid is demonstrated to be likely during the crystallization of a dense basal magma ocean, and retention of such melts is consistent with currently available experimental constraints. Calculated seismic velocities and densities of lower mantle material containing low‐abundance metallic liquids match the observed LLSVP properties. Small quantities of metallic liquids trapped at depth provide a natural explanation for primitive noble gas signatures in plume‐related magmas. Our model hence provides a mechanism for generating large‐scale chemical heterogeneities in Earth's early history and makes clear predictions for future tests of our hypothesis. Key Points: A 0.3–3% metallic melt can produce the features of the large low shear velocity provinces Trapping of metallic melt is likely during the crystallization of a dense basal magma ocean Large low shear velocity provinces can become a primordial geochemical mantle reservoir